Assessment of timeliness, representativeness and quality of data reported to Italy's national integrated surveillance system for acute viral hepatitis (SEIEVA). Issue 5 (May 2015) - Tosti, M.E.; Longhi, S.; de Waure, C.; Mele, A.; Franco, E.; Ricciardi, W.; Filia, A.
Abstract Objectives Periodic assessment of surveillance systems is recommended to verify whether they are appropriately monitoring the public health problem under surveillance. The aim of this study was to evaluate timeliness, data quality and representativeness of data reported to the Italian Integrated Epidemiological System for Acute Viral Hepatitis (SEIEVA). Study design Cross-sectional analysis of surveillance data. Methods Quantitative indicators were used to evaluate representativeness of reported cases, data quality, and timeliness between surveillance steps, for reports of acute viral hepatitis cases with date of onset of symptoms from 2009 to 2012 (N = 4516). Results Representativeness was 75%. Over 95% of records reported information on age, sex, city of residence, risk factors for hepatitis A and vaccination status. Information on risk factors for hepatitis B and C were reported less consistently (83%), as was information on early outcome (60%). Wide delays were found between surveillance steps. Conclusions The system collects high quality data on acute viral hepatitis cases in Italy. Timeliness was found to be the main limit and needs to be improved by optimizing web-based reporting procedures, increasing communication with participating centres, improving feedback and increasing dissemination of surveillance results. The study highlights the importance of reporting timeliness to detect outbreaks of acute viral hepatitis.